Planning and Facilitating Working Sessions with Evaluation Stakeholders. Issue 149 (March 2016) - Torres, Rosalie T.
Abstract: Facilitation is the process of bringing together, engaging, and following up with stakeholders resulting in new insights, perspectives, and potential actions, which (a) in all likelihood would have not otherwise occurred and (b) advance the interests of the stakeholder group. The most critical element of a successfully facilitated working session is the extent to which all potential influences are addressed during a planning phase. The chapter explains 15 interdependent components for successfully facilitated working sessions and includes a case example that describes the planning, execution, debriefing, and intended follow‐up to one session. It concludes by addressing (a) issues that arose in the session and how they related to information that was or was not available during planning and (b) the facilitation approaches/techniques used to address those issues.